The Effect of Social Media Promotion on Customer Loyalty Tekun.id Garut - Safitri, Lusiana Nur (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya (UPR), 2024)
Social media is a forum that is widely used by marketers in disseminating information about a product to consumers. The purpose of this study was to examine the effect of social media promotion on customer loyalty Tekun.id Garut. The method in this study uses quantitative methods. The population in this study were Tekun.id Garut consumers. The number of samples taken in this study amounted to 97 samples. The data collection technique was carried out using a questionnaire. The analysis methods in this study include validity and reliability tests, simple linear regression analysis. The results of this study state that social media promotion has a significant positive effect on consumer loyalty Tekun.id Garut.